Analisis dampak pembelajaran dalam jaringan (daring) terhadap kompetensi sosial dan kepribadian pada guru sekolah dasar - Izah Mukti Ferlina; Idam Ragil Widianto Atmojo; Roy Ardiansyah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The purpose of this research was to analyze the impact of online learning on the social competence and personality of teachers at SD Negeri Purwotomo No. 97 Surakarta during the Covid-19 Syndemic. This research is a case study qualitative research. The research subject was a grade II teacher at SD Negeri Purwotomo No.97 Surakarta. Data collection techniques are observation, interviews, and questionnaires. The data validity used source and technique triangulation techniques. Data analysts use data reduction, data presentation, and drawing conclusions. The impact of online learning on the social competence of teachers include the decreased ability of teachers to communicate and get along with students, increase the ability of teachers to communicate and interact effectively with parents, increase the ability of teachers to be inclusive, act objectively, and not discriminate against students and parents/guardians of students, increasing the ability of teachers to be active, creative, and fun, and teachers do not take advantage of the use of other communication technologies. The impact of online learning on the teacher's personality competencies include increasing responsible attitudes, decreased teacher discipline in starting learning on time, and less able teachers to be good role models for students. The conclusion of this research that online learning has a positive and negative impact on social competence and teacher personality.Kata kunci: online learning, social competence, personality competence, primary school